La0.6Sr0.4Co0.2Fe0.8O3-δ oxygen electrodes for solid oxide cells prepared by polymer precursor and nitrates solution infiltration into gadolinium doped ceria backbone. Issue 11 (September 2017) - Chrzan, Aleksander; Karczewski, Jakub; Gazda, Maria; Szymczewska, Dagmara; Jasinski, Piotr
Abstract: Infiltration is a method, which can be applied for the electrode preparation. In this paper oxygen electrode is prepared solely by the infiltration of La0.6 Sr0.4 Co0.2 Fe0.8 O3‐δ (LSCF) into Ce0.8 Gd0.2 O2-δ (CGO) backbone. The use a polymer precursor as an infiltrating medium, instead of an aqueous nitrate salts solution is presented. It is shown that the polymer forms the single-phase perovskite at 600 °C, contrary to the nitrates solution. As a result, obtained area specific resistance (ASR) is lowered from 0.21 Ω cm 2 to 0.16 Ω cm 2 at 600 °C. More than 35% of LSCF in the oxygen electrode decreases the performance.